Banding together for a cause : proven strategies for revenue and awareness generation - Armbruster, Rachel, 1975- (Hoboken, N.J. : Wiley, 2012)
'Experience the yellow wristband campaign from the beginning and learn how to position your nonprofit for success Passionate and inspiring, Banding Together for a Cause will help you identify ways to generate funds for your programs and missions through valuable and meaningful partnerships. In it, author Rachel Armbruster dissects the LIVESTRONG campaign, from timing and brand, to partners and visionary thinking. Engaging and informative, this reliable guide contains interviews and insights with key executives at both LIVESTRONG and Nike. Along the way, this remarkable book takes you behind-the-scenes of the spectacularly successful Lance Armstrong Foundation campaign. It starts with a simple big idea, the yellow wristband, and examines how you can find similar success within your own nonprofit. Focuses on this unforgettable fundraising campaign from a nonprofit perspective Offers the strategy as well as the tactics for nonprofits to feel that success is within reach Presents a variety of perspectives from the wildly successful LIVESTRONG campaign Learn from the yellow wristband. Banding Together for a Cause shows you how'--
Includes bibliographical references (p. 219) and index.
Keywords: Nonprofit organizations -- Management; Social responsibility of business; Strategic alliances (Business)